Enhancement of basic tennis technical skills: Game and drill training methods of male athletes reviewed by age group - Putri, Alifia Ramadhina; Sugiyanto; Riyadi, Slamet (Journal Sport Area, 2024)
Background Problems: The lack of variety in exercises applied by coaches makes players feel bored, so they must be given training variations by looking at training methods that significantly improve basic tennis technique skills between game training methods and drills. Research Objectives: This study aims to determine differences in the effect of game and drill training methods on improving basic tennis technical skills based on the age groups of 10-12 years and 13-15 years. Methods: In this context, the method used was experimental research with a 2x2 factorial design. The sample consisted of 24 male athletes in Lampung who were separated into 4 groups. Findings and Results: (i) There are differences in the effect of game practice and drill methods on improving basic tennis technique skills. (ii) There is a difference in improving basic tennis technique skills between the age groups of 10-12 years and 13-15 years. (iii) There is an influence of interaction between training methods and age groups on improving basic tennis technique skills. Conclusion: The age group 10-12 years is more appropriate if given the game training method, and the age group 13-15 years is more appropriate if given the practice training method. The findings of this study provide an important contribution by highlighting the importance of both applied training methods for basic tennis technique. This training method is also adapted for age-based characteristics. Therefore, the recommendation to use game and drill training methods as part of tennis training can help athletes cope with intense playing conditions. Based on the analysis above, the novelty of the research developed by the researcher was two exercise methods compared, two age groups that were sampled, and research instruments using International Tennis Number (ITN) On Court Assessment. Researchers used game and drill training methods that could affect the sample after treatment. Different from previous research, the sample used was male athletes aged 10-15 years.